PERAN BIRO PERJALANAN WISATA SUNRISE HOLIDAY TOUR & TRAVEL DALAM MENINGKATKAN MINAT WISATA KE GUNUNG BROMO - Alvianna, Stella (Jurnal Pariwisata Pesona, 2017)
Indonesian tourism contributes substantial foreign exchange to the state. Business actors in the field of tourism industry include travel agency, hotel, tourist transportation, restaurants and souvenir center. Travel agency helps the development of the tourism industry by arranging travel activities for tourists who want to travel with travel purposes. One of them is destinations in East Java that must be visited by foreign tourists namely Mount Bromo and Ijen Crater. The ways of promotion of a travel agency also contribute to the existence of the tourist bureau itself. More and more media campaigns conducted so many more destinations are known to many people in the country and abroad.